Ethiopia’s “Radio Voice of the Gospel” (1963-1977) in Context – Some Historical Observations on International Short Wave Radio Broadcasting to and from Sub-Saharan Africa - Palo, Mika (Africana Studia, 2020)
Radio Voice of the Gospel (RVOG) was a major international Christian missionary radio station based in Addis Ababa, Ethiopia. Owned and operated by the Lutheran World Federation, it transmitted programmes in altogether twenty languages to Africa and Asia during the years 1963- 1977. RVOG was an ecumenical project in which churches of various denominations – from Protestants to the old Ethiopian Orthodox Church – participated. This article attempts to clarify RVOG’s role and particularly its setting in the ideological “battle for the minds” fought on the busy radio waves over Sub-Saharan Africa in the 1960’s and 1970’s. The development of international short wave radio broadcasting and the involvement of Christian churches and organizations in it since the 1920’s is described briefly. A closer historical look is taken at broadcasting in Ethiopia as well as at international radio broadcasts originating from Africa. Keywords: History of Christian Missions, History of Radio Broadcasting, Contemporary History of Ethiopia/Sub-Saharan Africa